EDUCAÇÃO DA POPULAÇÃO NEGRA NO BRASIL: INTERDIÇÕES, RESISTÊNCIAS E AÇÕES AFIRMATIVAS - Pereira de Oliveira, Jaqueline (2024)
The article in question aims to reflect sociologically on the possibilities of access to formal education for the black population in Brazil from the 1824 constitution. Through bibliographical research and content analysis of legislation related to educatio, will be addressed formal prohibitions and conditions that made it impossible or difficult for that group to have access to formal education will be addressed, as well as the strategies that were forged by the black population at different times so that they could have access to education. By problematizing the consequences imposed by these barriers, will be highlighted the importance of implementing affirmative action in Brazil will be highlighted.